(untitled) (International Journal of Scientific Trends, 2026)
This article analyzes the socio-philosophical paradigms of harmony between national traditions and modernization processes in the renewing society of Uzbekistan. Particular attention is paid to the preservation of national values and adaptation to the requirements of modern development in the context of globalization, digitalization, and social transformation. The author evaluates national traditions as an important factor ensuring the spiritual stability of society and interprets modernization not only as a technical and economic process but also as a process of cultural and spiritual renewal. The article also reveals the philosophical essence of the principle of "national form and modern content". Within the framework of the Development Strategy of New Uzbekistan, the dialectical connection between national identity, the preservation of spiritual heritage, and ensuring innovative development has been scientifically substantiated. The research results demonstrate the theoretical and practical significance of ensuring the harmony of tradition and modernization within the national development model.